Education and training of crisis management and civil protection workers in the Slovac Republic - Lucia, Kováčová; null, null; Kavan, Štěpán; Marián, Mesároš; Peter, Lošonzi (International multidisciplinary scientific geoconference SGEM, 2018)
The aim of this article is analyse the current state of education and training of crisis management and civil protection workers in the Slovak Republic. Within the introduction part, we have discussed the role and activities of civil protection units, which is significant component of the Integrated Rescue System in the Slovak Republic. The article also focuses on the analysis on the current state of civil protection units in crisis management. An important part is the analysis of education process of crisis management and civil protection workers in the condition of the Slovak Republic.
Vzdělávání a příprava krizového managementu a pracovníků civilní ochrany v Slovenské republice
Keywords: Crisis management; Civil Protection; Integrated Rescue System of the Slovak Republic; Education and Training.; krizové řízení; civilní ochrana; integrovaný záchranný systém Slovenské republiky; vzdělávání a školení.